2010
DOI: 10.2308/jis.2010.24.1.43
|View full text |Cite
|
Sign up to set email alerts
|

How Do Investors Value IT? An Empirical Investigation of the Value Relevance of IT Capability and IT Spending Across Industries

Abstract: Drawing on the resource-based theory of the firm and using Ohlson’s (1995) residual income valuation framework, this paper investigates the relationships between IT capability and IT spending, and market value. We also assess whether these relationships differ based on the industry type (i.e., high-tech). Using publicly available ratings, and after controlling for firm-specific determinants as well as industry fixed-effects, we find that IT capability is value relevant (i.e., the stock market values of firms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 60 publications
0
25
1
5
Order By: Relevance
“…Regarding firm size, we found that structural trajectories (ITC  PPL) are similar between larger and smaller firms , although this differs from studies that indicate a positive association (K. Kim, Xiang, & Lee, 2009;Muhanna & Stoel, 2010). These results enable us to understand that isolated amount of resources and standardized IT [captured by size] are not the elements that provide competitive differential (Thouin et al, 2009;Ting-Peng et al, 2010), but the way resources are gathered and used in the organizations in terms of internal IT capabilities do so (Soto-Acosta & Meroño-Cerdan, 2008).…”
Section: Discussioncontrasting
confidence: 55%
“…Regarding firm size, we found that structural trajectories (ITC  PPL) are similar between larger and smaller firms , although this differs from studies that indicate a positive association (K. Kim, Xiang, & Lee, 2009;Muhanna & Stoel, 2010). These results enable us to understand that isolated amount of resources and standardized IT [captured by size] are not the elements that provide competitive differential (Thouin et al, 2009;Ting-Peng et al, 2010), but the way resources are gathered and used in the organizations in terms of internal IT capabilities do so (Soto-Acosta & Meroño-Cerdan, 2008).…”
Section: Discussioncontrasting
confidence: 55%
“…This dual perspective on performance has also been used in other studies (Tallon and Kraemer 2007). The combination of exogenous financial measures and directly reported perceptual measures helps provide a linking of evidence, going from IT investments via a firm's management capabilities (e.g., Muhanna and Stoel 2010;Tanriverdi 2006) to the perceptual impact of IT on important business goals and finally to the impact on financial performance. Prior research has also shown a significant correlation between perceptual measures of IT business value measures and financial performance (e.g., Tallon & Kraemer 2007) including ROA and ROE (Bharadwaj 2000;Wang et al 2008) or Tobin's Q (Aral and Weill 2007;Hitt and Brynjolfsson 1996).…”
Section: Defining Business Impactmentioning
confidence: 99%
“…Predominantemente, as pesquisas utilizam dados de desempenho e de TI de empresas em países desenvolvidos (A. S. Bharadwaj, 2000;Muhanna & Stoel, 2010;Stoel & Muhanna, 2009), sendo restritas as investigações em países em desenvolvimento, como o Brasil. Características da indústria e da economia nesses dois grupos de países poderiam sinalizar para diferenças no valor da TI (Muhanna & Stoel, 2010;Stoel & Muhanna, 2009).…”
Section: Introductionunclassified